Methods for assessing the adoption of rice varieties and land use changes in Chitwan, Nepal, using global positioning system transects and focus-group discussions - Joshi, Krishna D.; Khanal, Nabraj; Rawal, Krishna B.; Upadhyay, Santosh; Devkota, Krishna P.; Joshi, Govind R.; Witcombe, John R. (Frontiers in Sustainable Food Systems, 2023)
Rice varietal adoption was assessed using randomly selected global positioning system (GPS) coordinates in Chitwan district, Nepal. At pre-determined sampling points along the transects, which researchers located using GPS, data were collected on land use and the name of any rice variety grown. These data were then triangulated through focus group discissions (FGD) for each transect. The first two surveys were done in 2005 and 2006 in 14 transects with 440 GPS coordinates representing the major rice growing areas of Chitwan. Using the same approach, a third survey was conducted in 2022 in 72 out of the 440 GPS coordinates to document rice varietal adoption dynamics over a 16-year period. Farmers had changed the rice varieties they grew, but they continued to grow two to three old-improved varieties that covered more than 40% of the land. Hence, despite large changes in the rice varieties grown, the weighted average age of the varieties over 16 years was not reduced significantly. Despite their lower yields compared with newly released varieties, the older popular varieties persisted as they were in demand by the rice millers who have little motive to replace rice varieties for which they have an established market. The adoption of rice varieties released in the previous 15 years was low except for Sawa Masuli sub-1, a stress-tolerant rice variety, that was adopted in 16% of study area more than a decade after its official recommendation. This variety had the advantage of having similar grain characteristic to the established variety Sawa Masuli so millers could easily replace it with the new variety. The study revealed that premium rice lands in Chitwan were replaced with cattle and poultry farms, fishponds, and vegetables. Rice lands with better drainage and close to the Mahendra Raj Marg (highway), had been converted into real estate and settlements. There was a good agreement between the data collected from the sampled GPS coordinates and the FGDs. Random selection of GPS coordinates and sampling points is an unbiased, rapid, and efficient method for assessing adoption of agricultural technologies, varietal dynamics and changes in natural resources management and land use.